A lost tribe in the city: health status and needs of African asylum seekers and refugees in Hong Kong. Issue 1 (December 2016) - Wong, William; Cheng, Sealing; Holroyd, Eleanor; Chen, Julie; Loper, Kelley; Tran, Lynn; Miu, Heidi
Abstract Background Hong Kong's resistance to be a signatory of the 1951 Geneva Convention and lack of domestic policies in this area has resulted in restrictions on access to healthcare amongst asylum seekers and refugees (ASRs). Using social determinants of health framework this study sought to identify health practices, problems and needs of African ASRs in Hong Kong. Methods A cross-sectional survey comprising of six domains including health status, health-seeking behaviour and social experience targeted at adult African ASRs in Hong Kong was conducted through three local non-governmental organisations between February and April 2013. Outpatient care and inpatient care in the past 12 months were used as proxy measures of general and severe ill health respectively. Associations between the determinants of health factors with general or severe health was explored through logistic regressions. Results Majority of 374 participants were young, single, educated males having been in Hong Kong for over 5 years. A third of ARS (36.1 %) screened positive for depression. Most reported problems related to basic necessities (64.7–78.6 %) and access to health services (72.2 %). ASRs with relatively less education, health awareness or higher risk behaviours were less likely to have obtained outpatient or inpatient services. African ASRs reporting problems with case officers (aOR = 2.80; 95 % CI = 1.35-5.79) or illness in the past 30 days (aOR = 6.00; 95 % CI = 2.94-12.25) were more likely to report general ill health. Similarly, problems with the case officers (aOR = 3.76; 95 % CI = 1.97-7.18) and self-reported illness in the past 30 days (a​OR = 3.32; 95 % CI= 1.68-6.57) were also significantly associated with severe ill health. At the health system level, those who reported experiencing difficulties accessing the medical services in Hong Kong are 3.29 (95 % CI = 1.48-7.31) and 4.12 (95 % CI = 1.73-9.79) times as likely to report general and severe ill health respectively. Conclusion The host government should have moral and ethical obligations to attend to the health needs of ASRs. Evidently a number of structural and health system factors have significantly impacted the health of African ASRs in Hong Kong. Changes to current policies regarding how African ASRs are handled whilst in Hong Kong but, more immediately, improvements in healthcare access are needed.